AIAA Scitech 2020 Forum 2020
DOI: 10.2514/6.2020-0133
|View full text |Cite
|
Sign up to set email alerts
|

Application of Variational Asymptotic Method for Structural Analysis of Fan Rotor Blades in Boundary Layer Ingesting Flow Field

Abstract: Boundary Layer Ingestion (BLI) appears to be a promising technology for reducing aircraft fuel burn. Despite potential benefits, there are several challenges associated with BLI. A primary concern is the structural integrity of the fan blades experiencing unsteady forces due to unequal work input from the rotor at different circumferential locations of the engine annulus. In the conceptual design phase, rapid turnaround is as important as measuring the stresses accurately. Through the present work, the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Hence, the rotor blades would structurally demonstrate a non-linear transient behavior analyzed using GEBT while the blade's cross-sectional properties are evaluated using VABS. In prior work, Gupta et al 42 demonstrated that VAM (VABS + GEBT) is effective for structural analysis of fan blades subjected to dynamic loads. The authors compared the results produced by VAM to those from 3-D solid elements finite element method.…”
Section: Computation Of Structural Constraintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the rotor blades would structurally demonstrate a non-linear transient behavior analyzed using GEBT while the blade's cross-sectional properties are evaluated using VABS. In prior work, Gupta et al 42 demonstrated that VAM (VABS + GEBT) is effective for structural analysis of fan blades subjected to dynamic loads. The authors compared the results produced by VAM to those from 3-D solid elements finite element method.…”
Section: Computation Of Structural Constraintsmentioning
confidence: 99%
“…The fan rotor blade's stress due to unsteady loads was shown to have a maximum error of 12% while being more than 100 times faster. 42 Referring to Figure 4, the structural analysis block receives the unsteady loads and the blade geometry and checks for structural integrity. The analysis will give a time history of stresses and strains experienced by the blade due to the loads.…”
Section: Computation Of Structural Constraintsmentioning
confidence: 99%
See 1 more Smart Citation